Validation of the nickel biotic ligand model for locally relevant species in Australian freshwaters. (28th August 2018) - Peters, Adam; Merrington, Graham; Schlekat, Christian; De Schamphelaere, Karel; Stauber, Jennifer; Batley, Graeme; Harford, Andrew; van Dam, Rick; Pease, Ceiwen; Mooney, Tom; Warne, Michael; Hickey, Chris; et al.
Abstract: Australian freshwaters have relatively low water hardness and different calcium (Ca) to magnesium (Mg) ratios compared with those in Europe. The hardness values of a substantial proportion of Australian freshwaters fall below the application boundary of the existing European nickel biotic ligand models (Ni BLMs) of 2 mg Ca/L. Toxicity testing was undertaken using Hydra viridissima to assess the predictive ability of the existing Ni BLM for this species in extremely soft waters. This testing revealed an increased competitive effect of Ca and Mg with Ni for binding to the biotic ligand in soft water (<10 mg CaCO3 /L) than at higher water hardness. Modifications were made to the Ni BLM by increasing the binding constants for Ca and Mg at the biotic ligand to account for softer waters encountered in Australia and the more important competitive effect of Ca and Mg on Ni toxicity. To validate the modified Ni BLM, ecotoxicity testing was performed on 5 Australian test species in 5 different natural Australian waters. Overall, no single water chemistry parameter was able to indicate the trends in toxicity to all of the test species. The modified Ni BLMs were able to predict the toxicity of Ni to the test species in the validation studies in natural waters better than the existing Ni BLMs. The present study suggests that the overarching mechanisms defining Ni bioavailability to freshwater species are globally similar and that Ni BLMs can be used in all freshwater systems with minor modifications. Environ Toxicol Chem 2018;37:2566–2574. © 2018 SETAC